NEUROGENETICS OVERVIEW OF MENTAL HEALTH DISORDERS: SCHIZOPHRENIA, BIPOLAR DISORDER, AND DEPRESSION (Vietnam Journal of Community Medicine, 2026)
ABSTRACTObjective: To provide a structured narrative review of updated evidence on the neurogenetics of common mental health disorders, specifically schizophrenia, bipolar disorder, and depression.Method: A structured narrative review was conducted by identifying high-impact studies from 2021-2025 via PubMed and Google Scholar. Ten selected articles focusing on genome-wide association studies (GWAS), polygenic risk scores (PRS), and gene-environment interactions were synthesized to come to conclusions on the neurogenetic architecture of these disorders.Result: Mental health disorders, particularly the three studied, are formed by a complex polygenic architecture. Genetic variations contribute to biological vulnerability, which, when interacting with adverse environmental factors and psychological resilience, can trigger or exacerbate symptoms through changes in neural structure and function.Conclusion:Understanding of neurogenetics not only clarifies aspects of disease causation but also supports mental health’s early diagnosis and personalized medicine.
Keywords: Neurogenetics; mental health disorders; schizophrenia; bipolar disorder; depression; movement-environment interactions; personalized medicine.